2014
DOI: 10.5005/jp-journals-10026-1123
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Dental Caries among the Adults Attending a Regional Referral Hospital in Tanzania

Abstract: Background: Dental caries remain the main oral disease with greatest socioeconomic impact that correlates with lifestyle specifically dietary patterns and oral hygiene practices. Being a cumulative process, the numbers of individuals affected increase with age. This study aimed at determining the occurrence of dental caries among adult patients attending a public regional hospital. Materials and methods:A cross-sectional studies involving 436 adult patients who attended at Musoma Referral Hospital for dental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…Furthermore, the higher number of participants with seven years of education could be a reflection of the government efforts to make primary school free and accessible to all [ 27 ]. The higher number of males in this study is contrary to findings reported in another study conducted among adults in Tanzania [ 28 ]. This difference could be attributed to the differences in study design and sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the higher number of participants with seven years of education could be a reflection of the government efforts to make primary school free and accessible to all [ 27 ]. The higher number of males in this study is contrary to findings reported in another study conducted among adults in Tanzania [ 28 ]. This difference could be attributed to the differences in study design and sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…As a matter of fact, dental caries is infectious multifactorial disease characterized by the progressive demineralization of the tooth, following the action of bacterial acid metabolism 5 . The role of genetics as one of the key risk factor predisposing an individual to dental caries, [13,14] cannot be over looked, but that does not imply that it is inheritable disease.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Oral diseases are amongst the most prevalent human diseases, affecting a significant proportion of world's population, [4] and of this group of diseases, dental caries is the most common, characterized by the progressive demineralization of the tooth, following the action of bacterial acid metabolism. [5] Since time immemorial, the oral cavity, and the face have held seemingly inherent fascination for mankind which were affected by cultural customs, habits, beliefs, superstitions and taboos. [6] Due to the lack of knowledge, and in attempt to explain occurrence of disease, man established misconceptions, myths and taboos with regards to diseases including the oral diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Dental caries occur when the balance between its protective and risk factors is disturbed (Peneva, 2007). Socio-demographic factors like female gender (Namal et al, 2008;Singh et al, 2014), increasing age (Patro et al, 2008;Orji, 2015;Kahar et al, 2016;Maqsood et al, 2017) and low income (Costa et al, 2013), as well as behavioural factors such as frequent consumption of refined sugar, inadequate or lack of exposure to fluoride in toothpaste and drinking water, poor personal oral hygiene care (Tarvonen et al, 2017;(Chopra et al, 2015) and tobacco smoking (Patro et al, 2008), increase the risk of dental caries. By contrast, good oral hygiene and having good knowledge are protective factors (Tafere et al, 2018).…”
Section: Introductionmentioning
confidence: 99%